Computed tomographic characterization of the equine third metacarpal bone - Drum, Martha G., author (Colorado State University. Libraries, 2006)
Changes in subchondral bone (SCB) density attributable to disease pathogenesis or to normal aging and exercise related changes in horses are unclear. This project investigated equine (SCB) density characteristics using computed tomographic osteoabsorptiometry (CTO) and quantitative computed tomography (QCT). Results will provide objective measures of SCB density in horses. Five metacarpophalangeal joints were CT scanned and four 1-cm3 regions of interest were obtained for ash analysis to determine apparent bone density. A good correlation exists between 3D-QCT SCB densities and ash density in the distal third metacarpal bone of horses. Metacarpophalangeal joints from non-racing, exercised, and racing horses were CT scanned, disarticulated, and subjectively evaluated for gross pathologic damage. A 3D surface model and a model with eight surface ROIs of the distal third metacarpal condyle were created from the CT scans, with mean density and mean voxel standard deviation(MVSD) measured. CTO patterns of SCB density were assessed subjectively for distribution trends by applying colors to specific SCB density ranges. Racehorses had significantly lower mean density values than exercised and nonracing horses, and exercised horses had significantly lower mean density values than non-racing horses. Gross pathologic lesions were not associated with SCB density. Palmar abaxial sites were the only ROI with consistent significant differences between groups, and was supported by CTO maps. Finally, histologic lesions, gross pathologic lesions, and QCT bone density measurements in nine racehorses were compared. Histologic specimens were evaluated for presence of osteochondral lesions. Mean CT density proved to be of little value in predicting osteochondral lesions typical of racing horses. However, mean voxel standard deviation was mildly associated with osteochondral lesions in racing horses, and should be investigated in future studies with a larger sample size. QCT was a useful tool for characterizing SCB density in horses, but a poor predictor of gross pathologic change. CTO mapping contributed valuable SCB density characteristics in horses. While the predictive value of QCT and CTO was limited in this study, few pathologic lesions occurred in the sample. Even so, this study provides a foundation for using QCT and CTO prediction for larger studies on subtle joint disease in horses.
Keywords: anatomy and physiology; animals; radiology; veterinary services